Enhancing ICT Teachers' Competence with Nearpod : Transforming Interactive Learning Media in the Digital Age - Effendi, Hastria; Effendi, Hansi; Hendriyani, Yeka; Ranuharja, Fadhli; Novid, Igor; Saari, Erni Marlina (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aimed to enhance junior high school teachers' understanding and ability to utilize interactive learning media through the Nearpod platform conducted in collaboration with the Technology and Information Communication Subject Teacher Consultation (MGMP TIK) in the Fifty Cities Regency, involving 25 teachers from junior high schools and Islamic junior high schools as participants. The initiative employed the ABCDE method, encompassing five stages: (1) Assessment, (2) Building, (3) Collaboration, (4) Delivery, and (5) Evaluation. Data analysis included pre- and post-test comparisons, descriptive statistics, and questionnaire evaluations to assess knowledge improvement, performance, and interest in adopting Nearpod Evaluation results indicated a high level of interest and readiness among teachers to implement Nearpod in their instructional practices. The results showed a significant increase in post-test scores compared to pre-test scores, meeting the target of a minimum of 20% knowledge improvement. A total of 80% of participants were able to apply Nearpod effectively, and 75% demonstrated a high interest in integrating this technology into their teaching These findings suggest that Nearpod-based training is effective in improving teachers' competencies and digital skills, thereby holding the potential to strengthen educational quality in the digital era.